Computer System for Temperature Diagnostics of Cows (Agricultural Engineering, 2016)
The objective of the paper was to draw out a functional profile of a new computer system for temperature diagnostics of cows. This device enables oestrus detection including the silent one, early pregnancy (from the 5th day of insemination), acute inflammatory conditions and subclinical mastitis in a non-invasive manner during machine milking of cows. For diagnostic purposes one type of the measurement sensor was used, which is a unique feature in comparison to diagnostic devices mass produced and available on the market. A microprocessor module of the new milking system has intelligent devices features. It is construed of modern analogue and digital subassemblies and specialised measurement interfaces. The program structure of the system enables processing of automatically registered milk temperature values during cow milking on account of requirements of cow temperature diagnostics.